Challenges to urban cultural heritage conservation and management in the historic centre of Sulaimaniyah, Kurdistan-Iraq. Issue 3 (21st November 2016) - M. Amin, Hanaw M. Taqi; Adu-Ampong, Emmanuel Akwasi
Abstract : Purpose: The purpose of this paper is to examine the challenges to urban cultural heritage management conservation in the historical city of Sulaimaniyah, Kurdistan-Iraq. The paper focusses on the roles and interactions of stakeholders and the issues that confront the decision-making processes that underpin the management of historic city towns. Design/methodology/approach: A case study methodology is utilised for this research. It involves documentary analysis and interviews with stakeholders who are part of the management of the historic city centre of Sulaimaniyah, Kurdistan-Iraq. The findings from this case study are analysed in a systematic way before being discussed in the context of the literature on urban cultural heritage management. Findings: The research shows that although there is a shared vision of the need to preserve and conserve urban cultural heritage, the management process is a contentious one. Stakeholders have different ideas as to how to achieve conservation goals which leads to increasing conflicts among stakeholders. This situation is compounded by the limited financial resources available to local government agencies, political interference in the work of implementation agencies and the lack of capacity in local government to enforce rules and carry out conservation projects. There are also significant power differentials among stakeholders in the decision-making process which often means that local residents are excluded from the process of conserving their built urban heritage. Practical implications: This research can help practitioners who are in charge of urban cultural heritage management in dealing with stakeholder conflicts. The paper offers insight into a number of sources of stakeholder conflicts and on ways to overcome these in the planning process. Originality/value: The originality of research lies in the novelty of the case study area. This research highlights the issues of built heritage conservation management and planning practices in an area – Sulaimaniyah, Kurdistan-Iraq – that is geographically less represented in the extant literature. The research also identifies some of the key sources of conflict in urban heritage conservation projects and provides an insight into the roles of stakeholders in the management of smaller locally-dependent historic city centres.